Exploiting the resource-ratio (R*) hypothesis for weed management in legume crops: An example of volunteer Brassica napus in soybean - Geddes, Charles M.; Gulden, Robert H. (Frontiers in Agronomy, 2022)
Poor competitive ability and sensitivity to many herbicides create challenges for weed management in legume production. The resource-ratio (R*) hypothesis may provide insight into how to manipulate the competitive balance between nitrogen (N)-fixing legume crops and non-leguminous weed species. A field study was conducted to test whether the level of soil mineral N affected yield loss of an annual legume crop, soybean [Glycine max (L.) Merr.], in the presence of four different populations of an interfering non-leguminous weed, volunteer canola (Brassica napus L.), compared with a weed-free control. The experiment consisted of banding five rates of urea fertilizer (0–180 kg N ha-1) prior to seeding soybean and volunteer canola, and was repeated in three environments in Manitoba, Canada. Soybean yield remained unaffected by N rate in the absence of volunteer canola. Interference from the volunteer canola populations caused a linear decline in soybean yield by 2.6 kg ha-1 for every 1 kg ha-1 increase in soil mineral N. In the presence of volunteer canola, soybean yield decreased by 17% from the lowest to the highest soil mineral N. In the lowest-N conditions (30 kg residual-N ha-1), soybean yield was greatest (3,350 kg ha-1) and volunteer canola seed production and aboveground biomass were lowest (decline in canola seed production by 19%, 50%, and 74% of the maximum seed production in the 2015i, 2015ii, and 2016 environments, respectively). Therefore, growing legume crops like soybean on fields with lower soil mineral N may reduce interference from unmanaged non-leguminous weeds. As N fertilization intensifies interference of many weed species, tailoring weed management in legume crops around their capacity for N-fixation could provide the crop with a competitive advantage, thereby minimizing the impact of weed interference on legume crop yield.